The Effect of Adding Vegetable Waste to Feed on The Growth of Earthworms (Lumbricus rubellus) - Merta, I Wayan; Raksun, Ahmad (Jurnal Biologi Tropis, 2024)
Earthworms are invertebrate animals that live in the soil and are hermaphroditic. This animal requires organic materials as food. Research on the analysis of the growth of earthworms (Lumbricus rubellus) due to the addition of vegetable waste to feed has been carried out in Pagutan Village, Mataram City. This research aims to analyze (1) the effect of adding vegetable waste to feed on the number of earthworms, (2) the effect of adding vegetable waste to feed on the total weight of earthworms, (3) the best dose of vegetable waste so that earthworms can grow optimally. The earthworm growth parameters measured were the total number and total weight of earthworms at the end of maintenance. Research data was analyzed using analysis of variance. In this study it can be concluded: (1) adding vegetable waste (spinach, water kale, mustard greens and lettuce) to feed can increase the total number of earthworms, (2) adding vegetable waste to feed can increase the total weight of earthworms, (3) giving 2 liters of vegetable waste provided better growth results for earthworms compared to other treatments.